The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/path.2997
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NOTCH3 signalling significantly enhances sensitivity to cisplatin in EBV‐associated nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is an EBV-associated epithelial malignancy which is prevalent in south-east Asia and southern China. Despite the multiple genetic and epigenetic changes reported, the contribution of dysregulated signalling pathways to this distinct type of head and neck cancer is not well understood. Here we demonstrate the up-regulation of NOTCH ligands (JAG1 or DLL4) and effector (HEY1) in the majority of EBV-positive tumour lines and primary tumours. Among the NOTCH receptors, NOTCH3 was over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 31 publications
5
58
0
Order By: Relevance
“…It has also been reported that expression levels of Notch3 were increased in rat tracheal epithelial cells after treatment with 5-FU (20). NOTCH3 knockdown enhanced the sensitivity of nasopharyngeal carcinoma cells to CDDP treatment (21), and NOTCH3 overexpression correlated with shorter progressionfree/overall survival in patients with advanced stage ovarian carcinoma treated with platinum and taxane (22). In our data, NOTCH3 was upregulated in drug-resistant cells.…”
Section: Discussionsupporting
confidence: 80%
“…It has also been reported that expression levels of Notch3 were increased in rat tracheal epithelial cells after treatment with 5-FU (20). NOTCH3 knockdown enhanced the sensitivity of nasopharyngeal carcinoma cells to CDDP treatment (21), and NOTCH3 overexpression correlated with shorter progressionfree/overall survival in patients with advanced stage ovarian carcinoma treated with platinum and taxane (22). In our data, NOTCH3 was upregulated in drug-resistant cells.…”
Section: Discussionsupporting
confidence: 80%
“…These studies, like ours, underline the contextual complexity of Notch signaling and may inform prospective genotyping or screening criteria for future patient selection. Combinatorial use of Notch-targeted strategies with cytotoxic agents has shown encouraging clinical efficacies in ovarian cancers (5457) and nasopharyngeal carcinoma (58). Hence, Notch-targeted approaches in combination with conventional or current state-of-the-art pathway-specific targeting strategies poise tremendous potentials as new therapeutic regimens in treating melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Tamella and colleagues [9] revealed that VEGFR-3 upregulation in endothelial tip cells, caused by inhibition of the Notch signalling pathway, played a crucial role in sprouting angiogenesis in tumours. Since Notch inhibition has also been connected with the enhanced toxicity of cisplatin in colorectal cancer lines and nasopharyngeal adenocarcinoma [41,42], our results may indicate a similar pathophysiological mechanism for advanced esophagogastric cancer. The reason why oxaliplatin appeared to be less effective in VEGFR-3 positive patients remains unknown.…”
Section: Discussionmentioning
confidence: 53%